HARMONISATION OF LAND ECONOMIC POLICY: GEOSPATIAL DATA INTEGRATION AND INTER-INSTITUTIONAL SYNCHRONISATION - Yustinus Lambang Setyo Putro; Siti Nur Azizah; Gunawan Widjaja; Dyah Ersita Yustanti (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Land management in Indonesia still faces various fundamental problems, such as overlapping data, inconsistencies between institutions, and weak legal certainty, which have an impact on economic growth. Harmonising land economic policies through the integration of geospatial data and synchronisation between institutions is a strategic solution to improve bureaucratic efficiency, administrative transparency, and investment attractiveness. This study uses a literature review method by examining regulations, scientific articles, and institutional reports that discuss the role of spatial data and institutions in land policy. The results of the study show that harmonisation will only be achieved if both aspects run simultaneously, supported by political commitment, the use of information technology, increased human resource capacity, and clear regulatory support. Thus, the integration of geospatial data and inter-agency synchronisation can be the main instruments in realising a national land system that is accountable, inclusive, and effective for sustainable economic development.